TO THE QUESTION OF THE NEED OF EXPANSION OF THE ADMISSIBLE LIMITS OF JUDICIAL CONTROL IN THE CRIMINAL PROCESS OF RUSSIA (BY THE EXAMPLE CHOOSING A PREVENTIVE MEASURE IN THE FORM OF DETENTION) - Shadrina, Ekaterina; Rashidova, Asel; Ismailovа Karina; Rashidov, Sharaputdin; Omarova, Kamila (Revista Inclusiones, 2020)
The subject of the scientific article is the problem of expanding the admissible limits of judicial control at the pre-trial stages of Russian criminal proceedings by the example of a court allowing a petition for a preventive measure in the form of detention. The relevance of the investigated problem is determined by the need ofimprovementof the procedure of detention in order to ensure the constitutional rights of citizens and compliance with international standards in the field of protection of individual rights. The current procedure takes into account the need for the court to decide only the issue of law (formal grounds for making these decisions), but not the “question of fact” when deciding on detention or extending the terms of detention in custody — a minimum set of evidence of suspicion against a person or charges. An analysis of Russian court decisions on the selection of a preventive measure in the form of detention allows to assert that in each case the court, in support of the decision made, refers to the qualification of the actions of the suspect, the accused, contained in the petition of the prosecution, the interrogating officer, as well as in the materials submitted by the said entities, which can be deliberately “overstated,” and pays attention exclusively to the severity or special severity of the deed.